Radiation-Induced Coronary Artery Disease and Its Treatment: A Quick Review of Current Evidence - Christopher DeZorzi (Cardiology Research and Practice)
As advances in medical technology arise and the availability of cancer treatment increases, an increased number of patients are receiving cancer treatment. Radiation therapy has evolved to become one of the cornerstones of treatment for various types of cancers. One of the long-term consequences of radiation therapy is radiation-induced coronary artery disease (RICAD). Although the pathophysiology of RICAD may be slightly different and more acute onset than the commonly seen “generic” coronary artery disease, it is common practice to treat RICAD in the same method as nonradiation-induced CAD. This paper summarizes the current research available on the topic and shows there is not enough research to obtain significant data about outcomes and restenosis rates of PCI or outcomes of CABG in RICAD. The aim of this review is to create a concise and easy-to-follow review of the relevant data regarding RICAD and hopefully spark further interest in future studies in this field.